Experience and prospects in medical personnel informational training in IATP Center of SSMU scientific medical library in Tomsk - G. V. Zakharova; N. V. Molodtsova (Бюллетень сибирской медицины, 2003)
Training of users in SSMU scientific medical library is made on the basis of Internet Public Center that has been opened under the support of non-profit American corporation – “Project Harmony, Ink”. The teaching programs have been developed, subject seminars, courses and trainings are conducted. Graduates of change programs take part in the teaching process. The system of medical users training organization promotes the use of Internet resources as a source of medical and lawful information.